Analytical Solution of Equations Governing Aligned Plane Rotating Magnetohydrodynamic Fluid Through Porous Media by Martin’s Method - Birendra, Birendra Kumar Vishwakarma; Sil, Sayantan; Kumar, Manoj (IndoMS, 2024)
This investigation is an approach to setup an analytical solution of steady plane allied MHD fluid flow having infinite electrical conductivity in a rotating frame through porous media by Martin’s method. The governing non-linearequations of the fluid flow are transformed into a new form called Martin’s form by employing differential geometry where the curvilinear co-ordinates (Φ, Ψ) in the plane of flow shows that, the co-ordinate lines Ψ are the streamlines of flow and the co-ordinate lines Φ are arbitrary constants. Exact solution is obtained and velocity,vorticity, current density magnetic field and pressure distribution are found out. Also, the diagrams have been plotted to sketch the streamline patterns and to study variation of pressure function with angular velocity.